Perkembangan Dan Pola Literatur Maqāṣid Syarīʿah Di Malaysia: Analisis Sistematik - Ahmad Syukran Baharuddin; Wan Abdul Fattah Wan Ismail; Lukman Abdul Mutalib; Aiman Abdull Rahim; Siti Robiatun Addawiyah Roslan; Aminuddin Ruskam (INTELLIGENTIA RESOURCES, 2024)
Volume: 2 No. 1 (pp.38-55)